Advances in Swarm Intelligence First International Conference, ICSI 2010, Beijing, China, June 12-15, 2010, Proceedings, Part I - Tan, Ying.; Shi, Yuhui; Tan, Kay Chen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The books (LNCS 6145 and 6146) constitute the refereed proceedings of the International Conference on Swarm Intelligence, ICSI 2010, held in Beijing, China, in June 2010. T he 185 revised full papers presented were carefully reviewed and selected from 394 submissions. The papers are organized in topical sections on theoretical analysis of swarm intelligence algorithms, PSO algorithms, applications of PSO algorithms, ACO algorithms, applications of ACO algorithms, artificial immune system, novel swarm-based optimization algorithms, genetic algorithms, evolutionary computation, hybrid algorithms, multi-objective optimization algorithms, multi-robot systems, multi-agent based complex systems (part I) and fuzzy methods, applications of computational intelligence algorithms, signal processing and information security, information processing system, intelligent control, classifier systems, machine learning methods, other optimization algorithms, data mining methods, intelligent computing methods and applications, data mining algorithms and applications, other applications (part II).
Theoretical Analysis of Swarm Intelligence Algorithms -- PSO Algorithms -- Applications of PSO Algorithms -- ACO Algorithms -- Applications of ACO Algorithms -- Artificial Immune System -- Novel Swarm-Based Optimization Algorithms -- Genetic Algorithms -- Evolutionary Computation -- Hybrid Algorithms -- Multi-objective Optimization Algorithms -- Multi-robot Systems -- Multi-agent Based Complex Systems.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computation by Abstract Devices; Computer Communication Networks; Information Storage and Retrieval